2015
DOI: 10.1111/inr.12232
|View full text |Cite
|
Sign up to set email alerts
|

Older people's experiences of care in nursing homes: a meta‐synthesis

Abstract: Aim To integrate the current international knowledge and enhance our understanding of the experiences of older people of being cared for in nursing homes. Background There is a lack of integrated knowledge to help face the challenge of providing care to older people in nursing homes. Understanding the experiences of older people regarding their own care leads to interventions for reducing older people's suffering, while living in nursing homes. Methods Keywords describing the experiences of being cared for in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 26 publications
5
52
0
6
Order By: Relevance
“…It was common for residents to report having little opportunity to exert day‐to‐day choice within the facility. This is concerning, given consistent findings within the literature of the importance of autonomy in later life (Vaismoradi et al, ), and established associations between residents' autonomy and both adjustment and mental health (Brownie et al, ; Davison, McCabe, Knight, & Mellor, ). In contrast to residents' perceptions of their care, staff reported that they were aware of the importance of autonomy and aimed to enhance autonomy as a core component of their person‐centred care approach.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…It was common for residents to report having little opportunity to exert day‐to‐day choice within the facility. This is concerning, given consistent findings within the literature of the importance of autonomy in later life (Vaismoradi et al, ), and established associations between residents' autonomy and both adjustment and mental health (Brownie et al, ; Davison, McCabe, Knight, & Mellor, ). In contrast to residents' perceptions of their care, staff reported that they were aware of the importance of autonomy and aimed to enhance autonomy as a core component of their person‐centred care approach.…”
Section: Discussionmentioning
confidence: 67%
“…Previous research has indicated that regimentation and loss of privacy and autonomy are major obstacles to residents' adjustment to RAC (Lee et al, ). In addition, it has been suggested that organisational rules and processes impact on residents' perceptions of care (Vaismoradi, Wang, Turunen, & Bondas, ). Within this context, the current findings highlight the importance of staff finding ways to organise daily routines and provide consistency without being restrictive or overly rigid.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, insufficient trainers and a lack of standardized training are important factors affecting the quality of care (Woo, Milworm, & Dowding, 2017). There are an increasing number of studies on residents' experiences and satisfaction with nursing home care (Vaismoradi, Wang, Turunen, & Bondas, 2016). Hence, more emphasis should be placed on nursing staff education, training and supervision in an attempt to promote quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…One meta‐synthesis investigating the experiences of people in nursing homes found it to be somewhat imperfect . Quotes from each of the studies analyzed in the meta‐synthesis highlight the positive experiences of some people: “Since they have to do things, what I value most is that they [the care staff] go about them with good will.” However, it also highlighted several negative experiences: “at times, it seems they move us like furniture. They're all rushing, non‐stop… they must satisfy their timetable needs; therefore if they need to take everyone to breakfast they do.”…”
Section: Taken From Ransom S (2000) This Table Denotes the Findings mentioning
confidence: 99%